Fuzzy Mamdani for Equality of Employee Salary - Fakharudin, Panji Rangga Adzan Fajar; Avianto, Donny (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Every job in a coffee shop has a salary. Salary is a form of recognition or imbalance for the results achieved. Salary is often also called wages, which is an imbalance in the services provided regularly to employees. Fuzzy has several methods, one of which is Fuzzy Mamdani which is used to make inferences or take the best decision in a problem that has subtle values. In 1975, Ebrahim Mamdani proposed the Fuzzy Mamdani method. Fuzzy Mamdani is a method that uses linguistic rules and has a fuzzy algorithm so that it can be explained mathematically and is easy to understand. The input values for the criteria for length of work are 8, experience 8, and dependents 4. The output is based on Fuzzy Mamdani's calculations, the employee gets a salary of IDR 2.21 million. The results of this study research that the wage income offered by Warkop IN`DA to its employees is good and not far from the minimum wage of the coffee shop. This third variable has a big influence on the final calculation results. The system created is quite good because the MAE result is 0.567 and the MAPE result is 36.720%.